2019
DOI: 10.1183/13993003.00008-2019
|View full text |Cite
|
Sign up to set email alerts
|

Tropism of influenza B viruses in human respiratory tract explants and airway organoids

Abstract: Despite causing regular seasonal epidemics with substantial morbidity, mortality and socioeconomic burden, there is still a lack of research into influenza B viruses (IBVs). In this study, we provide for the first time a systematic investigation on the tropism, replication kinetics and pathogenesis of IBVs in the human respiratory tract.Physiologically relevant ex vivo explant cultures of human bronchus and lung, human airway organoids, and in vitro cultures of differentiated primary human bronchial epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
4
31
0
1
Order By: Relevance
“…Numerous studies used primary cells to show differences in replication of engineered and isolated influenza viruses (Bui et al, 2019;Danzy et al, 2014;Elderfield et al, 2014;Fischer et al, 2015;Gerlach et al, 2017;Monteagudo et al, 2019;Wohlgemuth et al, 2017). Here, we report that hNECs were more permissive for growth of virus isolates than MDCK cell cultures.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous studies used primary cells to show differences in replication of engineered and isolated influenza viruses (Bui et al, 2019;Danzy et al, 2014;Elderfield et al, 2014;Fischer et al, 2015;Gerlach et al, 2017;Monteagudo et al, 2019;Wohlgemuth et al, 2017). Here, we report that hNECs were more permissive for growth of virus isolates than MDCK cell cultures.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, influenza B effectively infected and replicated in human lung transplant, showing its ability to cause severe lower respiratory tract infections which are often associated with the lethal disease. Interestingly, one striking difference that was observed in this study was the dependency of viral replication on mucin, which selectively inhibited influenza B but not influenza A strains [8]. Cell surface mucin, specifically MUC-1, is upregulated in lung infections.…”
mentioning
confidence: 56%
“…These data strongly refute the claims that influenza B is the milder version of the flu. In this issue of the European Respiratory Journal, the study by BUI et al [8] sheds light on influenza B interactions within the human respiratory tract and lung to demonstrate its pathogenicity and its potential to spread and cause severe lung infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe influenza B accounted for 63% of all influenza cases in the 2017-2018 epidemic season [8]. A number of studies using ex-vivo (explant) cultures of human bronchus or lung have shown that IBV are capable of causing severe lower respiratory tract infections; these frequently lead to fatal complications [9].…”
Section: Introductionmentioning
confidence: 99%